Tick-borne rickettsiosis in Russia: current issues in the diagnosis - E. I. Krasnova; A. N. Vyazhevich; V. V. Provorova; V. G. Kuznetsova; N. I. Khokhlova; Z. A. Khokhlova (Лечащий Врач, 2023)
Background. For many years in Russia, the problem of diagnosing natural focal infectious diseases transmitted by ticks, including rickettsiosis, has persisted. The main rickettsial tick-borne pathogen in the Far East, Altai Territory and Western Siberia is Rickettsia sibirica, which causes tick-borne typhus, or tick-borne rickettsiosis. Diseases of Astrakhan spotted fever, caused by Rickettsia conorii subsp.caspiensis, are also detected in Russia and Kazakhstan. The emergence of new rickettsioses, for example, those caused by Rickettsia heilongjiangensis, Rickettsia raoultii, Rickettsia helvetica, Rickettsia aeschlimannii, Rickettsia slovaca, is explained by the diversity and wide distribution of tick species that carry rickettsia, and the evolution of the pathogen.Results. The article presents data on the epidemiology, pathogenesis and pathomorphology of tick-borne typhus. It has been shown that tick-borne typhus is manifested by a characteristic symptom complex – fever, primary affect at the site of tick suction, regional lymphadenitis, maculopapular profuse polymorphic rash, with possible damage to various organs. In typical cases, the diagnosis of tick-borne typhus can be made clinically and epidemiologically. The course of the disease is often benign, but complications of tick-borne typhus can include serous meningitis, pneumonia, and myocarditis. Antibodies to the antigens of tick-borne rickettsiosis pathogens are formed in the blood no earlier than 7-15 days after the onset of the disease due to the low immunogenicity of rickettsia, therefore verification of the diagnosis using the serological methods of RSK and RNGA is significantly delayed. New diagnostic approaches for CST are based on the use of ELISA and PCR methods. The development of molecular diagnostic methods has facilitated the identification of new rickettsia species. Data are presented on cases of rickettsiosis caused by Rickettsia raoulti in residents of Novosibirsk, diagnosed using the PCR method and registered for the first time in Russia.Conclusion. Early diagnosis of tick-borne rickettsioses is of great practical importance for timely and adequate antibacterial therapy. The development of new approaches to identify rickettsia through detection of genetic material with the further development of a method based on DNA amplification is promising for early diagnosis of rickettsial diseases, studying the pathogenesis and persistence of rickettsia, as well as ecological and epidemiological analysis.